(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes modern approaches to assessing the efficiency of industrial enterprises, where the criteria of financial and economic activity are of key importance. These indicators serve as a reliable basis for assessing the quality of management. Special emphasis is placed on the comprehensive nature of the analysis, which covers not only the performance indicators of the company itself, but also its partners. To assess the efficiency of energy enterprises, it is recommended to conduct a detailed data analysis using a variety of analytical methods and using an up-to-date information base.